Zinc Oxide–Porphyrin Hybrid Rhombuses: Catalytically Active Microstructures via Self‐Assembly. (29th May 2017) - Düring, Jasmin; Bernhardt, Sarah; Gröhn, Franziska
Abstract: A novel self‐assembled organic–inorganic hybrid structure consisting of zinc oxide and two oppositely charged porphyrins, showing significantly enhanced photocatalytic activity, is presented. Electrostatic self‐assembly of the cationic tetra‐( N ‐methyl‐4‐pyridyl)porphyrin (TMPyP) with preformed assemblies of ZnO nanorods and the anionic tetra‐(4‐sulfonatophenyl)porphyrin (TPPS) in ethanol results in porphyrin microrhombuses decorated with ZnO nanorods. The structure formation is followed spectroscopically. The shape of the microrhombuses and the number of attached ZnO nanoparticles can be tuned through the porphyrin ratio TMPyP/TPPS. An enhanced and selective catalytic activity is found, giving insight into the degradation mechanism. Due to the tool‐box principle and its versatility, the concept may have great impact in fields such as solar‐energy conversion and optoelectronics. Abstract : Organic–inorganic hybrid microrhombuses with enhanced photocatalytic performance can be built from two oppositely charged porphyrins and ZnO nanoparticles by self‐assembly in solution. They exhibit a tunable shape and enhanced catalytic activity.